Neue SEPSIS-3-Definition: Müssen wir Sepsis in Zukunft behandeln, bevor wir sie diagnostizieren dürfen? = New Sepsis-3 definition: Do we have to treat sepsis before we can diagnose it from now on? - Schmoch, Thomas; Uhle, Florian; Brenner, Thorsten; Weigand, Markus A. (Der Anaesthesist, 2017)
The Third International Consensus Definitions for Sepsis and Septic Shock (Sepsis-3) have been available since the beginning of 2016. SEPSIS-3 completely replaces the old SIRS criteria in the definition of sepsis and defines sepsis from now on as “life-threatening organ dysfunction caused by a dysregulated host response to infection”. However, it seems questionable whether in clinical practice the new definition is really superior to the old one. The most important question is the following: Is it helpful to have a definition that first recognizes a patient once organ dysfunction has occurred and the patient already needs intensive care?
First online: 11 May 2017
Gesehen am 15.06.2018